Nasolabial Aesthetics Following Cleft Repair: An Objective Evaluation of Subjective Assessment. (October 2019) - Kantar, Rami S.; Maliha, Samantha G.; Alfonso, Allyson R.; Wang, Maxime M.; Ramly, Elie P.; Eisemann, Bradley S.; Shetye, Pradip R.; Grayson, Barry H.; Flores, Roberto L.
Objective: Assess the weight and contribution of each of the parameters of the Asher-McDade Scale to overall subjective assessment of nasolabial aesthetics following cleft lip repair. Design: Retrospective cohort evaluation. Setting: Cleft and craniofacial center. Participants: Forty-one patients who underwent unilateral cleft lip repair. Interventions: Unilateral cleft lip repair. Main Outcome Measures: Nasolabial rating using the Asher-McDade scale and overall subjective assessment of nasolabial aesthetics using a rank score following unilateral cleft lip repair. Results: Strong interrater reliability was observed between the 3 raters. Significant association was determined on bivariate analysis between nasal form score (β = 27.06; P < .001), nasal symmetry score (β = 26.41; P < .001), nasal profile score (β = 28.75; P < .001), vermilion border score (β = 13.40; P = .012), and the ranking score. Adjusted β coefficients obtained from multivariate regression analysis were used to develop a modified nasolabial appearance score (over 5), that is, weighted for each of the 4 parameters: nasal form (over 8, adjusted β = 14.33), nasal symmetry (over 5, adjusted β = 7.96), nasal profile (over 5, adjusted β = 9.44), and vermilion (over 2, adjusted β = 3.31). Regression analysis between our modified nasolabial appearance score and patient ranking score demonstrated superior goodness of fit when compared to the Asher-McDade overall nasolabial appearance score ( R 2 = .80; P < .001 vs R 2 = .69; P < .001). Conclusion: The parameters evaluated in the Asher-McDade scale have different weights and contribute differently to overall subjective assessment of nasolabial aesthetic outcomes following cleft lip repair. Adjusting for their weights results in a modified score that demonstrates superior correlation with overall subjective assessment of nasolabial aesthetic outcomes.